Evidence that knock down of GSK-3β in Chronic Myelogenous Leukemia cells augments IFN-γ-induced apoptosis. (December 2020) - Kauffman, Melissa R.; Nazemidashtarjandi, Saeed; Ghazanfari, Davoud; Allen, Abigail E.; Reynolds, Nathan M.; Faik, Ahmed; Burdick, Monica M.; McCall, Kelly D.; Goetz, Douglas J.
Highlights: Role of IFN-γ in apoptosis of Chronic Myelogenous/Myeloid Leukemia (CML) is unclear. Glycogen synthase kinase–3 (GSK-3) has been implicated in cell death and survival. IFN-γ induces modest apoptosis in a CML cell line. CML cells in which GSK-3β is knocked down exhibited enhanced IFN-γ induced apoptosis. Suggests GSK-3β protects against IFN-γ induced apoptosis of CML cells. Abstract: The role of interferon-gamma (IFN-γ) in Chronic Myelogenous/Myeloid Leukemia (CML) and in the treatment of CML remains unclear; specifically, the effect of IFN-γ on apoptosis. There is reported interplay between IFN-γ and glycogen synthase kinase–3 (GSK-3), a kinase which has been implicated in both cell death and, conversely, cell survival. Thus, we utilized the CML-derived HAP1 cell line and a mutant HAP1 GSK-3β knocked-down cell line (GSK-3β 31bp) to investigate whether GSK-3 modulates IFN-γ's action on CML cells. Significantly less GSK-3β 31bp cells, relative to HAP1 cells, were present after 48 h treatment with IFN-γ. IFN-γ treatment significantly decreased GSK-3β 31bp substrate adhesiveness (relative to HAP1 cells); an observation often correlated with cell death. Fluorescence microscopy revealed that IFN-γ induces a modest level of apoptosis in the HAP1 cells and that IFN-γ induced apoptosis is significantly enhanced in GSK-3β 31bp cells. Utilizing a complementary GSK-3β knocked-down cell line (8bp) we found, via flow cytometric analysis, that IFN-γ induced apoptosis is significantly enhanced in GSK-3β 8bp cells relative to HAP1 cells. Combined, our findings suggest that IFN-γ induces apoptosis of CML cells and that loss of GSK-3β significantly augments IFN-γ-induced apoptosis.